2005
DOI: 10.1111/j.1365-2966.2005.09811.x
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of primordial magnetic fields by anisotropic gravitational collapse

Abstract: If a magnetic field is frozen into a plasma that undergoes spherical compression, then the magnetic field B varies with the plasma density ρ according to B∝ρ2/3. In the gravitational collapse of cosmological density perturbations, however, quasi‐spherical evolution is very unlikely. In anisotropic collapses the magnetic field can be a much steeper function of gas density than in the isotropic case. We investigate the distribution of amplifications in realistic gravitational collapses from Gaussian initial fluc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Additional to any dynamo action, further support for strong magnetic field amplification during the process of structure formation comes from the application of the Zel'dovich approximation (Zel'dovich 1970) to follow the MHD equations during the gravitational collapse (Bruni et al 2003;King and Coles 2006). These papers demonstrate the existence of a super-adiabatic amplification due to the anisotropy of the collapse of the LSS within the cold dark matter paradigm.…”
Section: Approximative Simulationsmentioning
confidence: 98%
“…Additional to any dynamo action, further support for strong magnetic field amplification during the process of structure formation comes from the application of the Zel'dovich approximation (Zel'dovich 1970) to follow the MHD equations during the gravitational collapse (Bruni et al 2003;King and Coles 2006). These papers demonstrate the existence of a super-adiabatic amplification due to the anisotropy of the collapse of the LSS within the cold dark matter paradigm.…”
Section: Approximative Simulationsmentioning
confidence: 98%
“…As seen below, cooling also provides a sustained turbulent regime in the core and the corresponding additional field amplification. Based on the Zel'dovich approximation of gravitational dynamics, King & Coles (2006) predict that a cosmological magnetic field should evolve as a B ∝ ρ 0.87 , due to anisotropic collapse in a Gaussian random field. This compares favourably with the low-density part of our simulation (see Fig.…”
Section: Simulationsmentioning
confidence: 99%
“…More detailed numerical studies have found that in realistic large‐scale structures without special geometries the amplification of the seed field is not quite as expected from these simple collapse models, with a rough power‐law dependence but a higher value of α (Dolag et al 1999, 2005; Roettiger et al 1999). King & Coles (2006) showed that an average over small‐scale collapses leads to an average value of α which is higher than the isotropic value α= 2/3; the average of a non‐linear function is not the same as the non‐linear function of the average. Moreover, other phenomena, such as mergers and anisotropies, act to enhance the field still further.…”
Section: Numerical Calculationsmentioning
confidence: 99%